2012
DOI: 10.4049/jimmunol.1102084
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Epithelial Cell-Derived Semaphorin 7A Negatively Regulates Development of Colitis via αvβ1 Integrin

Abstract: The intestinal immune system is constantly challenged by commensal bacteria; therefore, it must maintain quiescence via several regulatory mechanisms. Although intestinal macrophages (Mϕs) have been implicated in repression of excessive inflammation, it remains unclear how their functions are regulated during inflammation. In this study, we report that semaphorin 7A (Sema7A), a GPI-anchored semaphorin expressed in intestinal epithelial cells (IECs), induces IL-10 production by intestinal Mφs to regulate intest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 42 publications
5
57
0
Order By: Relevance
“…We have not explored the contribution of Sema 7a expression on other cells, such as macrophages and epithelial cells, both of which are important drivers of Sema 7a-mediated T-cell activation (6,8) and fibrosis (24,31). Our study does not determine the receptor through which Sema 7a affects TGF-b1-induced lung fibrosis, although we have previously shown that Sema 7a's effects on human fibrocytes and murine lung fibrosis occur in a b1 integrin-dependent manner (9).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…We have not explored the contribution of Sema 7a expression on other cells, such as macrophages and epithelial cells, both of which are important drivers of Sema 7a-mediated T-cell activation (6,8) and fibrosis (24,31). Our study does not determine the receptor through which Sema 7a affects TGF-b1-induced lung fibrosis, although we have previously shown that Sema 7a's effects on human fibrocytes and murine lung fibrosis occur in a b1 integrin-dependent manner (9).…”
Section: Discussionmentioning
confidence: 82%
“…Semaphorin 7A (Sema 7a) is a glycophosphatidylinositolanchored membrane protein that is required for axon track formation during embryonic development (4,5). Sema 7a also regulates inflammatory responses via stimulation of macrophage chemotaxis and cytokine production (6), dendritic cell migration and chemokine expression (7), modulation of T-cell function (6)(7)(8), and regulation of collagen production by fibrocytes (9). Hematopoietic expression of Sema 7a is sufficient to induce fibrosis in TGF-b1-induced murine lung fibrosis (9); however, the mechanism(s) mediating these effects remain unknown.…”
Section: Conclusion: Sema 7amentioning
confidence: 99%
“…This is likely mediated, at least in part, through the Plexin C1 receptor ( Figure [ Plexin C1 itself propagates the infiltration of immune cells into sites of sterile pulmonary inflammation and also during Zymosan A-induced inflammation [38,39]. By contrast, Sema7A was also found to be protective during dextran sulfate sodium (DSS)-induced colitis, where it increased the production of the anti-inflammatory cytokine IL-10 through the anb1 integrin receptor [40]. Therefore, the action of Sema7A is likely to be dependent on the expression of its target receptors within specific organ systems.…”
Section: Ngps [ 4 7 3 _ T D $ D I F F ] Expressed In Endothelial Cellsmentioning
confidence: 89%
“…Integrin are heterodimers composed of the a-and b-subunits. In intestinal macrophages, interaction between avb1-integrin and Sema 7A produces IL-10 31) . Sema 7A initiates T-cell-mediated inflammatory responses through 11-integrin via FAK and MAPK activation 32) .…”
Section: Expression Of Semaphorin 7a Receptors During Osteogenic Diffmentioning
confidence: 99%